Some context of the multifunctional agricultural and sustainable rural development - Horváth, Péter; Nagy, Géza (Acta Agraria Debreceniensis, 2012)
The paper first negotiates the concept of multifunctionality, then the main steps of the development of the connection between agriculture and rural development are discussed. It presents the situation of a most disadvantageous sub-region that is aided by a complex program. The local rural resources are estimated by the multifunctional rural resource analysis method considering threefold function of the rural areas. It is concluded, that the land use systems and labour-intensive cropping systems have specific missions in multifunctional agriculture and rural development in the sub-region.